Physiologic and productive responses of Holstein dairy cows with access to the constant or limited shade - Damasceno, J. C.; Baccari, F.; Targa, L. A. (Revista Brasileira Zootecnia Brazilian Journal Animal Sci, 1998)
The work: was carried out to evaluate the physiologic and productive responses of 16 Holstein breed cows, in different lactating stages and production levels, maintained in two free stall corral types, with or without plastic sheet covering, in the southeast-northwest of the covered area edges. The animals were confined in free stall system, during the months of the summer, with access to the constant or Limited shade. A complete randomized experimental design was: used. The physiological variables measured were respiratory frequency (morning an afternoon) and rectal temperature (morning and afternoon). The productive variables were milk production (morning, afternoon and daily), dry matter (DM) intake (% live weight) and efficiency of milk production (kg of milk/kg DM intake). The animals with access to the constant shade presented respiratory frequency (74.1 vs 81.0 breath/min.) and rectal temperature (39.5 vs 39.7 degrees C) lower and mirk production (22.6 vs 20.9 kg/day) and efficiency of milk production (1.3 vs 1.2 kg of milk/kg DM ingested) higher than the animals with access to the limited shade. There was no effect on the dry matter intake.
Keywords: thermal comfort; heat stress; respiratory frequency; milk production; rectal temperature; dairy cows